2000
DOI: 10.1164/ajrccm.162.3.9907048
|View full text |Cite
|
Sign up to set email alerts
|

Deep Inspiration-induced Bronchoprotection Is Stronger than Bronchodilation

Abstract: We have previously shown that in healthy subjects, deep inspiration (DI) has not only a bronchodilatory but also a bronchoprotective effect that is absent in asthmatic subjects. We conducted the study reported here to test the hypothesis that the bronchoprotective effect is stronger than the bronchodilatory effect, and to determine the extent to which these two effects are related. Ten healthy subjects underwent provocations in which single doses of methacholine, previously shown to reduce FEV(1) by 10% to 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
111
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 16 publications
10
111
0
Order By: Relevance
“…Two recent studies (10,21) reported that a series of five deep breaths taken before the inhalation of a single dose of MCh dramatically and exclusively protected healthy humans from airway narrowing. The conclusion was based on the fact that the decrements of FEV 1 and FVC after a bolus of MCh were significantly less when the constrictor agent was preceded by deep breaths than when it was not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies (10,21) reported that a series of five deep breaths taken before the inhalation of a single dose of MCh dramatically and exclusively protected healthy humans from airway narrowing. The conclusion was based on the fact that the decrements of FEV 1 and FVC after a bolus of MCh were significantly less when the constrictor agent was preceded by deep breaths than when it was not.…”
Section: Discussionmentioning
confidence: 99%
“…RECENT STUDIES HAVE SHOWN that deep breaths taken immediately before inhalation of methacholine (MCh) greatly modulate the bronchoconstrictor response in normal (10,12,21) but not in asthmatic (10) subjects. This would suggest that the shortening capacity of airway smooth muscle is reduced by previous lung stretching in healthy subjects, and the lack of such a bronchoprotective mechanism may be responsible for airway hyperresponsiveness in asthma.…”
mentioning
confidence: 99%
“…The third possible answer stems from studies in which the protective effect of deep inspirations taken before experimentally induced bronchoconstriction is examined [18,27,60,[65][66][67][68]. MALMBERG et al [65] were the first to notice that if a deep inspiration was taken shortly before (,6 min) acutely induced bronchoconstriction, the extent of airway narrowing during the induced constriction was reduced.…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 99%
“…Furthermore, they showed that this effect was greater when deep inspirations were taken before than after inhalation of methacholine. More recent work (44) has confirmed this finding and also shown that the bronchoprotective effect increases with the number of deep inspirations in normal subjects, but is totally absent in asthma (45). The limitation of these studies is that the changes in airway caliber were assessed by FEV 1 , which needs a deep inhalation to be measured.…”
Section: External Modulation Of Airway Narrowingmentioning
confidence: 83%